Academic or Apologetic Studies on the Qurʾan and Tafsīr: A Critical Analysis of Theses and Dissertations at the Graduate School of Syarif Hidayatullah State Islamic University (UIN) Jakarta (2019–2023) - Rahman, Yusuf; Zahasfan, Alvian Iqbal; Saifunnuha, Mukhamad; Nuryaman, Nuryaman (JURNAL INDO-ISLAMIKA, 2025)
This study critically evaluates Majid Daneshgar’s central thesis in Studying the Qurʾan in the Muslim Academy, which posits that Qurʾānic and tafsīr scholarship within Islamic universities predominantly manifests as normative-apologetic discourse rather than rigorous academic inquiry. Through a case study analysis of 2019-2023 graduate theses and dissertations from Syarif Hidayatullah State Islamic University (UIN) Jakarta, the research applies the methodological framework developed by Andrew Rippin, Aaron W. Hughes, and Daneshgar to distinguish between academic, normative, and apologetic studies. Findings reveal that the majority – though not entirety – of examined works demonstrate a predominantly apologetic orientation in their engagement with Qurʾanic texts and exegetical traditions. This systematic investigation contributes empirical evidence to ongoing scholarly debates about epistemological paradigms in contemporary Islamic higher education.